Fiskal Luar Negeri dan Penerapannya di Indonesia - Tansuria, Billy Ivan (JBE (Journal of Business and Economics); Volume 8 No.2, 2009 JBE UNKLAB, 2009)
Individuals as domestic tax prayers who do not posses Tax Identification Number (NPWP) will be imposed Income Tax as he or she leaves for abroad.  This kind of tax is known as Exit Tax.  This Exit Tax is categorized as and defined in Income Tax Regulation article 25 which is prepaid tax in nature.  It can be credited at the end of a fiscal year at the time the individuals or institutions submit annual tax report (SPT).  The purpose of this article is to present a brief description of the implementation of the Exit Tax, individuals who are or are not subjected to the Exit Tax, individuals who are exempted from the Exit Tax, the amount of Exit Tax implemented in Indonesia, and provisions on Exit Tax in the year 2010.